Variability of Punctuation Marks in English - Tigranyan, Lilit (Armenian Folia Anglistika, 2013)
The article analyzes the characteristics of the use of English punctuation marks, namely those of brackets and multi-points in three types of discourse – prose, drama and scientific prose. The functional value of punctuation marks is conditioned by a number of factors including the historical period, the discourse type, the writer’s style, to name just a few. The brackets and the multi-points, as a rule, perform different functions in the three types of discourse mentioned above.